Keragaman Morfologi Sukun (Artocarpus altilis Park. Fosberg) di Kecamatan Teluk Ambon - Pamungkas, Mar A S; Kesaulya, Henry; Jambormias, Edizon (Jurnal Agrosilvopasture-Tech, 2023)
The purpose of this study was to determine the diversity of breadfruit plants in the Ambon Bay District based on their morphological characteristics. The breadfruits plant descriptors used refer to the International Board Plant Genetic Resources Institute and key characterization and evaluation descriptors: Methodologies for the assessment of 22 crops. There are various morphological characteristics of breadfruit in 31 observational variables. At a similarity value of 27,47, three clusters were formed, namely the first cluster Rumah Tiga, Poka, the second cluster Wainani, Hunut, and the third cluster Tawiri, Hative Besar 2, and Hative Besar 1. Each cluster that forms into one cluster has relatively homogeneous characteristics, while between clusters have different characteristics.